Konsinyasi: Studi Tentang Konstruksi Hubungan Hukumdalam Perjanjian Antara Supplier House of Orchita dengan Toko Online PT. 8Wood Teleindo - Hapsari, Cindy Chyntia; , Kelik Wardiono, S.H., M.H; , M. Sandjoyo, SH. M.Hum (2015)
This research is a normative juridical research which is a legal construction from consignment agreement between House of Orchita as the supplier and the Online Store PT.8Wood Teleindo. The source of data used secondary data ehich is he consignment agreement. Data analysis technique applued qualitative analysis. The results of the research showed: 1) Legal construction of the consignment agreement which is between Online Store PT. 8wood Teleindo with the suppliers House of Orchita, is a voluntary with the care goods agreement. It is in according to the Section 1701 and 1702 KUHPerdata and the opinion of M. Yahya Harahap; 2) Legal protection for the supplier if any default in the execution of the consignment agreement: the first party will cease to display and / or sell product which belongs to the second party in the online store page, the second party may take back the products which are deposited. It is according to the article 1243 KUHPerdata and Subekti opinion.